2018
DOI: 10.3390/app8101829
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis for Performance Evaluation of a Multi-Functional CO2 Heat Pump Water Heating System

Abstract: In recent years, CO2 heat pump water heating systems have been developed, and their performances have been enhanced while their functions have been expanded. In a multi-functional system, used for both hot water supply and bath heating, hot water retrieved from the top of a storage tank is returned to its bottom or side after heat exchange for bath heating, which destroys the stratified temperature distribution in the storage tank and degrades the system performance. In this paper, the performance of a multi-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Liang et al [8] and Hu et al [9] presented the optimum design and a prediction model of heat exchangers. Other studies [10][11][12][13] reported various approaches for improving efficiency and to mitigate GHG emissions. All these studies are indispensable for continuous progress, and guarantee steady steps toward reducing direct and indirect emissions of GHGs.…”
Section: Fundamental Process Components and Mechanical Vapor Comprementioning
confidence: 99%
“…Liang et al [8] and Hu et al [9] presented the optimum design and a prediction model of heat exchangers. Other studies [10][11][12][13] reported various approaches for improving efficiency and to mitigate GHG emissions. All these studies are indispensable for continuous progress, and guarantee steady steps toward reducing direct and indirect emissions of GHGs.…”
Section: Fundamental Process Components and Mechanical Vapor Comprementioning
confidence: 99%
“…In addition, in arid regions, water is a sparse and valuable commodity, and water losses during fluid circulation can present a significant economic liability and burden on the ecosystem. A few recent studies point to the use and storage of CO 2 in various applications (see [1][2][3]).…”
Section: Introductionmentioning
confidence: 99%